Knowledge and attitude of Engaged and Recently Married Couples Toward Premarital Screening: A Cross-Sectional Study - Mokhtar abdo Almoliky; Heba Abdulrhman; Showqi Hasan Safe; Malak Galal; Heba Abdu; Basma Towfiq; Shatha Abdullah; Mohammed Waleed; Mujeeb A. Sultan (SAGE Publishing, 2022)
Background and Objective: Despite that inherited (thalassemia and SCA) and infectious (hepatitis B, hepatitis C and AIDs) diseases and their risk factor consanguineous marriage are widespread among Yemen population, community-based awareness studies towards premarital screening (PMS) is extremely limited, so our study is designed to elicit knowledge and attitude of engaged and recently married couples in Taiz (Yemen) toward PMS. Methods: A cross-sectional study was conducted from April to September 2021 at Taiz. A well-structured questionnaire was designed and then delivered to participants to collect data. Results: The results revealed that majority of respondents (83.60%-94.18%) had knowledge about inherited and infectious diseases, respectively, and educational institution was the main knowledge source. Females had significantly higher knowledge than males ( P ≤ .01), except about AIDs since no difference ( P = .539). The results also revealed that majority of respondents had positive attitudes toward PMS, except toward AIDs testing since 70% of males and 68.91% of females had negative attitudes. The majority of respondents agreed that screening reduces the diseases incidence. Approximately half of respondents (50.79%-56.61%) tend to go ahead for marriage in case of positive results for inherited and infectious diseases respectively. Making PMS as an obligatory step prior engagement was agreed by 47.62% of respondents (45.71% of males, 48.74% of females). Conclusion: A high level of knowledge and positive attitudes toward inherited and infectious diseases and PMS were reported. This knowledge reflected on the agreement of majority of respondents regarding PMS importance in term of reduction of diseases incidence.